2009
DOI: 10.1002/app.31433
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene–propylene–diene terpolymer/silica compound modification with organosilane [bis(triethoxysilylpropyl)disulfide] and improved processability and mechanical properties

Abstract: Bifunctional silane [bis(triethoxysilylpropyl)-disulfide (TESPD)] was added to a silica-containing ethylene-propylene-diene terpolymer mold compound, and its effects with respect to the vulcanization properties, processability, and physical properties were investigated. The addition of TESPD caused reduced heat generation during mixing, low minimum torque, low drop temperature, and low extrusion pressure buildup in the extruder. It also caused a high vulcanization torque, high torque rise, high torque maximum,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
1
6
0
Order By: Relevance
“…Compounds 1 and 4; Table ). It is interesting that a similar behavior was also reported by Kim who showed major improvement in the mechanical properties of an EPDM rubber after adding precipitated silica and a sulfur‐bearing liquid silane similar to TESPT.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…Compounds 1 and 4; Table ). It is interesting that a similar behavior was also reported by Kim who showed major improvement in the mechanical properties of an EPDM rubber after adding precipitated silica and a sulfur‐bearing liquid silane similar to TESPT.…”
Section: Resultssupporting
confidence: 81%
“…The bound rubber content also increased as a function of the silica loading though the increase was more significant when TESPT was present in the rubber. A similar study by Kim reported significant increases in the cross‐link density of an EPDM rubber when a bifunctional silane was added. The silane‐added compound showed a higher elongational modulus than the control one.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…Oxiranes are generally prepared using perbenzoic acid (9), chloroperbenzoic acid (10) and monoperphthalic acid (11). Performic acid is an extremely active organic peracid (12)(13)(14)(15)(16) used for the epoxidation, but, owing to its instability (17), it has to be prepared in situ.…”
Section: Introductionmentioning
confidence: 99%